An introduction to reservoir simulation using MATLAB/GNU Octave : user guide for the MATLAB Reservoir Simulation Toolbox (MRST) - Lie, Knut-Andreas (Cambridge : Cambridge University Press, 2019)
This book provides a self-contained introduction to the simulation of flow and transport in porous media, written by a developer of numerical methods. The reader will learn how to implement reservoir simulation models and computational algorithms in a robust and efficient manner. The book contains a large number of numerical examples, all fully equipped with online code and data, allowing the reader to reproduce results, and use them as a starting point for their own work. All of the examples in the book are based on the MATLAB Reservoir Simulation Toolbox (MRST), an open-source toolbox popular popularity in both academic institutions and the petroleum industry. The book can also be seen as a user guide to the MRST software. It will prove invaluable for researchers, professionals and advanced students using reservoir simulation methods. This title is also available as Open Access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 23 Jul 2019).
Keywords: Hydrocarbon reservoirs -- Computer simulation; Oil reservoir engineering -- Data processing; MATLAB; GNU Octave